ANALISIS FLUKTUASI EKSPOR BEBERAPA PRODUK PERTANIAN INDONESIA DI NEGARA MITRA UTAMA - Adrian D. Lubis (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2011)
developing countries ha ve built special safeguard mechanism (ssm) proposal in order to protect their agricultural products. By using seasoality method test, mann-Kendall test, and control chart, the study found out that export pattern of Indonesia’s agricultural products is not in line with the existing ssm proposal. the agricultural products of coffee and tea showed significant seasonal pattern of export to India’s market. other agricultural products of cacao and its processed products also presented significant seasonal pattern of export to malaysia, singapore and china . Meanwhile, vegetable oil and fats did not show significant seasonal pattern of export to importing countries. on the ssm proposal, Indonesia should promote the minimum level of 19.92 persen, which is higher than developing countries proposal of maximum 10%.